Examining the application of the Technology Acceptance Model (TAM) in Industry 5.0 adoption: An early outlook - Ahmad, Nur Azreen Farihah; Muhamad, Mira Qerul Barriah; Abdullah Thani, Ayu Kamareenna; Rosely , Nurhidayah; Ismail, An Nur Nabila; Nik Mohd Zainordin, Nik Mohamad Shamim (Journal of Islamic, Social, Economics and Development, 2025)
Business has grown rapidly in recent decades due to globalization and advancements in technology, especially in information technology (IT). Humanity is on the brink of a major technological shift that will transform how people live, work, and communicate—something never seen before. Manufacturing companies are currently transitioning into what is known as Industry 4.0. However, a new phase called Industry 5.0 is emerging, where humans and machines are working closely to create customized products and services that meet customer needs. As Industry 5.0 continues to expand, more research is needed in this field. Understanding how organizations perceive the usefulness and ease of using new technology is crucial for technology adoption. This study explores Industry 5.0 by focusing on how organizations decide to implement it, using the Technology Acceptance Model (TAM). The TAM model has been widely used in previous studies to analyze factors influencing the adoption of new technology. The insights from this research are valuable across multiple fields.